Which Neurons Will Be the Engram - Activated Neurons and/or More Excitable Neurons? - Kim, Ji-il; Cho, Hye-Yeon; Han, Jin-Hee; Kaang, Bong-Kiun (Experimental neurobiology, 2016)
During past decades, the formation and storage principle of memory have received much attention in the neuroscience field. Although some studies have attempted to demonstrate the nature of the engram, elucidating the memory engram allocation mechanism was not possible because of the limitations of existing methods, which cannot specifically modulate the candidate neuronal population. Recently, the development of new techniques, which offer ways to mark and control specific populations of neurons, may accelerate solving this issue. Here, we review the recent advances, which have provided substantial evidence showing that both candidates (neuronal population that is activated by learning, and that has increased CREB level/excitability at learning) satisfy the criteria of the engram, which are necessary and sufficient for memory expression.